Elucidating Divergent Spatiotemporal Load Dynamics: A Comparative Scrutiny of Urban versus Rural Smart‐Meter Electricity Profiles in the Kashmir Valley - Qawsain Hussain (PT. Radja Intercontinental Publishing, 2025)
This study conducts a comprehensive spatiotemporal analysis of electricity consumption patterns across urban (Lal Chowk) and rural (Kupwara) regions of the Kashmir Valley, integrating hourly load demand with environmental parameters such as temperature, humidity, and solar irradiance over a seven-day observational period. The results delineate distinct consumption behaviors shaped by socio-economic and infrastructural contexts. Urban load profiles exhibit a sharp and pronounced evening peak between 18:00 and 21:00, driven by simultaneous residential and commercial energy use, whereas rural profiles are characterized by dual moderate peaks—morning and evening—aligned with daylight-based activity cycles and limited appliance usage. Correlational analysis reveals a strong positive relationship between ambient temperature and load demand in the urban sector, indicating significant climate-responsive electricity use, particularly for cooling. In contrast, the rural load shows a more muted thermal sensitivity. Solar irradiance further differentiates demand patterns; urban loads remain consistently high throughout the day, while rural consumption displays mid-irradiance peaks and midday declines, reflecting task-based utilization and behavioral adaptations. Furthermore, a focused comparison of event day load (June 6) with regular days illustrates a marginal but notable increase in urban electricity use due to elevated evening activities, while rural demand remains relatively stable. These insights emphasize the critical need for region-specific energy planning, forecasting, and policy interventions in the context of evolving smart grid infrastructure and heterogeneous demand landscapes.